Identification of a novel AIFM1 variant from a Chinese family with auditory neuropathy - Wang, Rongrong; Bai, Xiaohui; Yang, Huiming; Ma, Jingyu; Yu, Shudong; Lu, Zhiming (Frontiers in Genetics, 2022)
Background: Auditory neuropathy (AN) is a specific type of hearing loss characterized by impaired language comprehension. Apoptosis inducing factor mitochondrion associated 1 (AIFM1) is the most common gene associated with late-onset AN. In this study, we aimed to screen the pathogenic variant of AIFM1 in a Chinese family with AN and to explore the molecular mechanism underlying the function of such variant in the development of AN. Methods: One patient with AN and eight unaffected individuals from a Chinese family were enrolled in this study. A comprehensive clinical evaluation was performed on all participants. A targeted next-generation sequencing (NGS) analysis of a total of 406 known deafness genes was performed to screen the potential pathogenic variants in the proband. Sanger sequencing was used to confirm the variants identified in all participants. The pathogenicity of variant was predicted by bioinformatics analysis. Immunofluorescence and Western blot analyses were performed to evaluate the subcellular distribution and expression of the wild type (WT) and mutant AIFM1 proteins. Cell apoptosis was evaluated based on the TUNEL analyses. Results: Based on the clinical evaluations, the proband in this family was diagnosed with AN. The results of NGS and Sanger sequencing showed that a novel missense mutation of AIFM1, i.e., c.1367A>G (p. D456G), was identified in this family. Bioinformatics analysis indicated that this variant was pathogenic. Functional analysis showed that in comparison with the WT, the mutation c.1367A>G of AIFM1 showed no effect on its subcellular localization and the ability to induce apoptosis, but changed its protein expression level. Conclusion: A novel variant of AIFM1 was identified for the first time, which was probably the genetic cause of AN in a Chinese family with AN.